2000
DOI: 10.1006/jmsc.1999.0637
|View full text |Cite
|
Sign up to set email alerts
|

Including predation mortality in stock assessments: a case study for Gulf of Alaska walleye pollock

Abstract: . 2000. Including predation mortality in stock assessments: a case study for Gulf of Alaska walleye pollock. -ICES Journal of Marine Science, 57: 279-293.A separable catch-age stock assessment model that accommodates predation mortality is applied to the Gulf of Alaska walleye pollock (Theragra chalcogramma) assessment. Three predators are incorporated in the model: arrowtooth flounder (Atheresthes stomias), Pacific halibut (Hippoglossus stenolepis), and Steller sea lion (Eumetopias jubatus). The effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 39 publications
4
91
0
2
Order By: Relevance
“…These single-species stock assessments are used to set the biological reference points that serve as the starting point for catch advice. Multispecies stock assessments have been conducted that provide time and age-varying estimates of M for some species (e.g., Livingston and Methot 1998;Hollowed et al 2000;Jurado-Molina et al 2005). These models generally provide some ecosystem considerations that have functionally served to evaluate the level of precaution built into the catch advice arising from the single-species stock assessments.…”
Section: Discussionmentioning
confidence: 99%
“…These single-species stock assessments are used to set the biological reference points that serve as the starting point for catch advice. Multispecies stock assessments have been conducted that provide time and age-varying estimates of M for some species (e.g., Livingston and Methot 1998;Hollowed et al 2000;Jurado-Molina et al 2005). These models generally provide some ecosystem considerations that have functionally served to evaluate the level of precaution built into the catch advice arising from the single-species stock assessments.…”
Section: Discussionmentioning
confidence: 99%
“…They can be an important source of standing biomass in an ecosystem and are often subject to both predation pressure and commercial harvesting. Various authors have found that when consumption of particular forage species is calculated, the predation mortality for the species that had been assumed as a part of the total natural mortality in traditional stock assessments was underestimated (e.g., Hollowed et al 2000;Moustahfid et al 2009b). Unsurprisingly, predation mortality is temporally and ontogenetically variable as well (Tsou and Collie 2001).…”
Section: How Species Respond To Multiple Impactsmentioning
confidence: 99%
“…A relatively new concern for management is emerging in regions where commercial fisheries co-occur with marine mammal populations that are recovering from historical over-harvesting [2]. Increases in natural predator numbers may be influencing prey populations in ways that concern conventional fisheries stock assessment and management [2,3]. Along the west coast of Vancouver Island (WCVI), British Columbia, Canada, for example, sea otters (Enhydra lutris) were successfully reintroduced in the 1970s, and their expanding populations may now conflict with the management of high-value invertebrate fisheries that developed in their absence [4].…”
Section: Introductionmentioning
confidence: 99%